2014
DOI: 10.1016/j.neo.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 Promotes Melanoma Cell Growth through Sox-2

Abstract: The prognostic value of the carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1) in melanoma was demonstrated more than a decade ago as superior to Breslow score. We have previously shown that intercellular homophilic CEACAM1 interactions protect melanoma cells from lymphocyte-mediated elimination. Here, we study the direct effects of CEACAM1 on melanoma cell biology. By employing tissue microarrays and low-passage primary cultures of metastatic melanoma, we show that CEACAM1 expression gradually increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…C). This adhesion molecule was already found to show gradually increasing expression from melanocytic nevi to metastatic specimens and to be a prognostic marker for melanoma . This proves that partial reprogramming of melanoma cells is a suitable system to find novel biomarkers for early melanoma progression and patient stratification.…”
Section: Discussionmentioning
confidence: 72%
“…C). This adhesion molecule was already found to show gradually increasing expression from melanocytic nevi to metastatic specimens and to be a prognostic marker for melanoma . This proves that partial reprogramming of melanoma cells is a suitable system to find novel biomarkers for early melanoma progression and patient stratification.…”
Section: Discussionmentioning
confidence: 72%
“…several studies have shown that normal melanocytes do not express CEACAM1 while most malignant melanoma lesions do express CEACAM1 (10,20). We previously demonstrated that up to 89% of metastatic melanoma lesions are positive for CEACAM1 (6,10) and that its expression increases concomitantly with tumor development and progression (10).…”
Section: Discussionmentioning
confidence: 91%
“…CEACAM1 is a transmembranal glycoprotein belonging to the Ig superfamily, composed of several extracellular Ig-like domains (7). CEACAM1 has been shown to be involved in the development of cancerous transformation, particularly in melanoma, yet also in non-small cell lung cancer and gastric carcinoma (8)(9)(10). Importantly, a strong correlation between CEACAM1 expression and the development of metastatic disease with poor overall survival was demonstrated in melanoma (11) and in lung cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…CEACAM1 is a glycoprotein belonging to the carcinoembryonic antigen (CEA) family that is expressed in a wide variety of cells [32]. The prognostic value of CEACAM1 in cancer is controversial: CEACAM1 expression correlates with good prognosis in mammary carcinomas, whereas in melanomas, upregulation of CEACAM1 is accompanied by poor overall survival [33,34]. It is notable that CEACAM1 was upregulated in the MCF-7/TxR cells and downregulated by CAP.…”
Section: Discussionmentioning
confidence: 99%